Spatial distribution of hydrogen sulfite and ammonia emissions from a wastewater treatment plant in Costa Rica, using the AERMOD air pollution dispersion model - Delgado-Villalobos, Andrea; Sibaja-Brenes, José Pablo; Zúñiga-Castro, Wilfred; Vega-Guzmán, Ilena; Alfaro-Solís, Rosa; Mora-Barrantes, José Carlos; Borbón-Alpízar, Henry (Uniciencia, 2023)
[Objective] The variation of hydrogen sulfide (H2S) and ammonia (NH3) concentrations in air was studied in a wastewater treatment system in Costa Rica to obtain information about the dispersion of odors produced using on-site measurements and an air dispersion model. [Methodology] Thirteen samples were taken in periods of 12 hours and 24 hours between October 2016 and February 2017, and the measurements taken in the field were entered into a dispersion model. Meteorological parameters including direction and wind speed, global radiation, temperature, percentage of relative humidity, precipitation, and atmospheric pressure were recorded. Dispersion of gases around the selected emission points in the treatment plant was determined using the Aermed View and AERMOD programs. Data on roughness parameters, Bowen ratio and albedo for a rural area were incorporated into the Aermet View and the data collected was incorporated into the AERMOD model. [Results] The concentrations of gases emitted by the plant were below the perception values of these substances, 0.70 µg/m3 (< 0.50 ppb) for H2S and 26.6 µg/m3 (< 35.5 ppb) for NH3. The discharge channel is the main source of emissions; the gases emitted were dispersed to the neighboring communities of La Carpio, María Auxiliadora and Rincón Grande to the Northwest; Carvajal Castro, Rossiter Carballo, Residencial Real Santamaría and Lagunilla to the Northeast, and the National Emergency Commission to the South. Error values ranged between 5% and 48% for H2S and between 8% and 75% for NH3. The concordance index (CI) showed agreement between the predicted and observed values for both H2S and NH3. [Conclusions] H2S and NH3 emissions from the wastewater treatment system do not represent a risk to health or the environment for nearby populations.